The Influence of Service and Relationship Quality to Satisfaction Consumer Reefer Container Meat in PT Company Indogal Trading - Agung Kwartama; Rizky Reynaldi (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
The purpose of this study is to examine the effect of service quality and relationship quality on consumer satisfaction that has an impact on consumers with their loyalty, especially in the distribution of meat reefer containers by PT Indogal Trading. The main problems identified are low loyalty and consumer satisfaction, on service issues such as late delivery, temperature fluctuations, and less than optimal complaint management. The study population consisted of 105 consumers of PT Indogal Trading in 2023 representing 50 companies, with a sample of 83 respondents using the simple random sampling method. Data collection by analyzing and collecting questionnaires with SMART PLS. The results of the study stated that service quality and relationship quality have a significant influence on consumer satisfaction and loyalty. In addition, consumer mediation of their satisfaction is specifically the influence of service quality and relationship quality on consumer loyalty. In conclusion, increasing service quality and relationships can significantly increase consumer satisfaction and loyalty. Managerial suggestions provided include increasing service consistency, better temperature management, and increasing responsiveness to consumer complaints to strengthen consumer loyalty.